Small intestinal dysmotility in cirrhotic patients: correlation with severity of liver disease and cirrhosis-associated complications - Gundling, Felix; Luxi, Margo; Seidel, Holger; Schepp, Wolfgang; Schmidt, Thomas (Zeitschrift für Gastroenterologie, 2020)
Introduction Altered small intestinal motility has been observed in various manometry studies in patients with cirrhosis. Since small bowel manometry is available only in a few centers, interpretation of dysmotility in cirrhosis is controversial.Patients and Methods In this study, both fasting and postprandial manometric tracings of 24-hour antroduodenojejunal manometries were analyzed using both visual analysis and computer-aided analysis.Results In 34 patients (83 %), the mean migrating motor complex (MMC) cycle length was different compared with healthy controls. Phase II was prolonged in 27 patients (66 %), while phase I showed a reduced duration in 23 (56 %) and in phase III in 13 individuals (32 %). We also observed special motor patterns, e. g., migrating clustered contractions (MCCs) or retrograde clustered contractions (RCCs), which were present during fasting (69 %) and postprandial (92 %) motility, while none of the healthy controls showed any special motor patterns. Special motor patterns showed a significant correlation with the severity of cirrhosis (Child-Score; p > 0.05) and the existence of ascites (p < 0.05).Discussion This study in a large cohort of patients with cirrhosis by using 24-hour, solid state portable manometry showed in most individuals disturbances of cyclic fasting motility. Special motor patterns like RCCs during fasting and postprandial motility could be observed exclusively in the cirrhosis group, showing a significant correlation with severity of cirrhosis and the occurence of associated complications.
Keywords: ascites; hepatic encephalopathy; liver cirrhosis; small bowel dymotility; small bowel manometry